Children's learning and development in conflict- and crisis-affected countries: Building a science for action. (May 2021) - Aber, J. Lawrence; Tubbs Dolan, Carly; Kim, Ha Yeon; Brown, Lindsay
Abstract: This paper critically reviews the opportunities and challenges in designing and conducting actionable research on the learning and development of children in conflict- and crisis-affected countries. We approached our review through two perspectives championed by Edward Zigler: (a) child development and social policy and (b) developmental psychopathology in context. The aim of the work was to answer the following questions: What works to enhance children's learning and development in such contexts? By what mechanisms? For whom? Under what conditions? How do experiences and conditions of crisis affect the basic processes of children's typical development? The review is based on a research–practice partnership started in the Democratic Republic of the Congo in 2010 and expanded to research in Niger and Lebanon in 2016. The focus of the research is on the impact of Healing Classrooms (a set of classroom practices) and Healing Classrooms Plus (an additional set of targeted social and emotional learning activities), developed by the International Rescue Committee, on children's academic outcomes and social and emotional learning. We sought to extract lessons from this decade of research for building a global developmental science for action. Special attention is paid to the importance of research–practice partnerships, conceptual frameworks, measurement and methodology. We conclude by highlighting several essential features of a global developmental science for action.